PENGARUH MEDIA PEMBELAJARAN BERBASIS APLIKASI CANVA TERHADAP MOTIVASI BELAJAR SISWA PADA PELAJARAN IPAS KELAS V DI SD GMIT 004 LAWAHING KECAMATAN MUTIARA KABUPATEN ALOR TAHUN PELAJARAN2024/2025 - Lakalapay, Maria; Badu, Khumaira M.; Galeko, Marzuki; Peka, Musrifa (Jurnal Edukasi, 2026)
The Effect of Canva Application-Based Learning Media on Student Learning Motivation in Fifth Grade Science at GMIT 004 Lawahing Elementary School, Mutiara District, Alor Regency, in the 2024/2025 Academic Year The purpose of this study was to determine the effect of Canva Application-Based Learning Media on Fifth Grade Science at GMIT 004 Lawahing Elementary School. The research method used was quantitative with an experimental approach. The results showed a significant difference in the post-test results between the control class and the experimental class, with average scores of 26.25 and 36.86, respectively. Furthermore, the average t-test results were also greater than the t-table value, which was 8.13 and 2.41, respectively. Therefore, Ho was rejected and Ha was accepted.